Value Conflicts and the (Post) Democratic Constellation of Society - Trenz, Hans-Jörg (PARTECIPAZIONE E CONFLITTO, 2024)
Western democracies rather than being consolidated are increasingly shattered by new value and identitarian conflicts. Instead of a widening consensus about core democratic values, we observe the intensification of value polarisation. Even European integration, which was meant to promote its core foundational principles to be embraced by member states and citizens across the European social and political space, continues, as shown by numerous opinion polls, to be divided by value clashes. In light of these contrasting experiences, I ask: How can we explain the new salience of value conflicts in democracy despite the postulated end of ideologies? What, if anything distinguishes value conflicts from old ideological polarisations? Drawing on empirical examples of social media polarisations, I will argue that such new value conflicts between polarised groups (e.g. liberals against anti-liberals) are to be understood as a continuation and not a discontinuation of old ideological divides. As such, they should be interpreted either as disruptions of existing democracy or as departure towards novel forms of democratic government and not as the heralds of a new age of post-democracy and post-ideology.